Kekuatan Sambungan Dan Ketahanan Korosi Melalui Penambahan Filler Zinc Pada Las Titik Dissimilar Antara Aluminium AL 1100 Dan Baja Tahan Karat SS 316 - Jumaniana Jaya, Gede Jovial; Budiarsa, I Nyoman; Putra Negara, Dewa Ngakan Ketut (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract Spot welding is a welding method that can be used to connect thin metal plates and can be applied to the automotive industry. There are several parameters that affect the strength of the resulting joint at a given point. Parameters that are known and can affect the results of welded joints in this study include the use of different joints on the metal, the diameter of the taper electrode used, the pressing time during the welding process, and the addition of zinc filler to the weld joint. The purpose of this study was to determine the strength of the welded connection through testing and the metal's resistance to corrosion at different joints between AL 1100 and SS 316 metals with the addition of zinc filler. The results of the data obtained from the shear test are the shear stress and strain. Welded joints that have the maximum shear stress are connections with variations (Ø7mm, 1s, zinc filler) with a maximum shear stress of 66.5 MPa. The results of the test are a visual assessment of corrosion of the metal and the rate of corrosion, as well as the efficiency of using zinc filler. On visual observation, the test sample without zinc filler experienced a significant change compared to the sample using zinc filler. The corrosion rate of the sample without zinc filler is 12,586 Mpy while the sample using zinc filler has a corrosion rate of 4,413 Mpy. So that this zinc filler has an efficiency of 64.9%. Based on the corrosion tests carried out, zinc filler as a sacrificial anode can work well in slowing the corrosion rate at different joints between AL 1100 and SS 316 metals. Keywords: dissimilar connection, spot welding, aluminum 1100, stainless steel 316, corrosion test, shear test